Some Aspects of Weighted Rayleigh Distribution - Zain, Saad A.; Hussein, Iden Hassan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper, we proposed a new class of weighted Rayleigh distribution based on two parameters, scale and shape parameters which are introduced in Rayleigh distribution. The main properties of this class are investigated and derived.